2016
DOI: 10.5966/sctm.2016-0035
|View full text |Cite
|
Sign up to set email alerts
|

Smooth Muscle Progenitor Cells Derived From Human Pluripotent Stem Cells Induce Histologic Changes in Injured Urethral Sphincter

Abstract: In vivo integration of smooth muscle progenitor cells (pSMCs) derived from human pluripotent stem cells was examined. pSMCs were derived from a human embryonic stem cell line and two induced pluripotent stem cell lines. The data suggest that hPSC‐derived pSMCs facilitate restoration of urethral sphincter function by direct smooth muscle cell regeneration and by inducing native tissue elastin/collagen III remodeling.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 22 publications
(34 citation statements)
references
References 49 publications
2
31
1
Order By: Relevance
“…Previous studies have observed significant changes in elastin and collagen content in the periurethral tissues of SUI women [50]. Consistent with these published data from human tissues, studies from our lab and others have showed that the protein level of elastin significantly decreased in lower urinary tract of SUI rats [28,51]. However, after treatment with MACS-sorted pSMCs, the tissue content of elastin in the lower urinary tract significantly increased, suggesting that, in addition to cell integration, elastin deposition in the damaged rat lower urinary tract may also contribute to the therapeutic effect of MACS-sorted pSMCs.…”
Section: Discussionsupporting
confidence: 90%
“…Previous studies have observed significant changes in elastin and collagen content in the periurethral tissues of SUI women [50]. Consistent with these published data from human tissues, studies from our lab and others have showed that the protein level of elastin significantly decreased in lower urinary tract of SUI rats [28,51]. However, after treatment with MACS-sorted pSMCs, the tissue content of elastin in the lower urinary tract significantly increased, suggesting that, in addition to cell integration, elastin deposition in the damaged rat lower urinary tract may also contribute to the therapeutic effect of MACS-sorted pSMCs.…”
Section: Discussionsupporting
confidence: 90%
“…The rat model of SUI was established via transabdominal urethrolysis as described by Rodriguez et al [25]. This SUI rat model showed signi cantly decreased urethral resistance (by leak point pressure measurements) and urethral smooth muscle damage for at least 8 weeks after surgery [17,26]. Bilateral ovariectomy was done on the rodents to eliminate the in uence of estrus cycle on the ECM metabolism and to simulate an estrogen-de ciency state of menopause [27].…”
Section: In Vitro Treatment Of Human Bladder and Vaginal Cells With Pmentioning
confidence: 99%
“…Total RNA (1 µg) was reverse transcribed into cDNA using the M-MLV reverse transcriptase system (Thermo Scienti c). PCR primers were described previously [17,24], except human TIMP2 (Sense: AAGCGGTCAGTGAGAAGGAA; Anti-sense: GATGTTCAAAGGGCCTGAGA), rat MMP2 (Sense: GTAAAGTATGGGAACGCTGATGGC; Anti-sense: CTTCTCAAAGTTGTACGTGGTGGA) and rat TIMP2 (Sense: ACACGCTTAGCATCACCCAGAA; Anti-sense: CAGTCCATCCAGAGGCACTCAT The slides were visually scored by four people separately for elastin length (1 = short, 2 = moderate, 3 = long), thickness (1 = thin, 2 = moderate, 3 = thick) and density (1 = sparce, 2 = moderate density, 3 = dense), collagen density (1 = sparce, 2 = moderate density, 3 = dense). The scorers were blinded to the group assignments.…”
Section: Rna Extraction and Quantitative Reverse Transcriptionpolymermentioning
confidence: 99%
See 2 more Smart Citations